PENGARUH DIFERENSIASI PRODUK TERHADAP KEPUTUSAN PEMBELIAN (STUDI PADA ROSEBERRY CAKE SHOP GARUT) - Suca Rusdian (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2021)
This research is motivated by the purchase decision at Roseberry Cake Shop Garut which is not optimal. One thing that can be done to improve purchasing decisions is through an appropriate product differentiation strategy. The purpose of this study was to determine the effect of product differentiation on purchasing decisions at Roseberry Cake Shop Garut. The methodology used is descriptive method with associative problem formulation. The data analysis technique used the validity instrument, the reliability instrument test, the Spearman rank correlation coefficient test, the determination coefficient test and hypothesis testing using SPSS Version 20 and the formula. Based on the results of testing and statistical analysis using the Spearman rank correlation test, there is a